Disabilities in Early Childhood: A Global Health Perspective - Bolajoko O. Olusanya; Claudine Storbeck; Vivian G. Cheung; Mijna Hadders-Algra (MDPI AG, 2023)
Prior to the launch of the United Nations' Sustainable Development Goals (SDGs) in 2015, childhood disability was rarely considered an important subject in global health. The SDGs till 2030 now require that children under 5 years who are at risk of not benefitting from inclusive quality education are identified, monitored, and promptly supported. A new tool for identifying children who are not developmentally on track has been developed by UNICEF but has limited sensitivity for detecting children with disabilities due to reliance on parental assessment of child behavior in certain everyday situations. In this paper, we identified conditions that are commonly associated with developmental disabilities based on the International Classification of Diseases (ICD) codes and clarified the concept of "developmentally on track" as it relates to children with developmental disabilities and developmental delays. We summarized the latest evidence on the global burden of developmental disabilities in children under 5 years based on the diagnostic and functional approaches for measuring disabilities at the population level. We highlighted the global health context for addressing the needs of children with developmental disabilities and provided an overview of the opportunities and the role of pediatric caregivers in supporting children with developmental disabilities.